2015
DOI: 10.3892/ijo.2015.3086
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of N-myc downstream regulated gene 1 caused by the methylation of CpG islands of NDRG1 promoter promotes proliferation and invasion of prostate cancer cells

Abstract: Current studies tend to consider N-myc downstream regulated gene 1 (NDRG1) as a tumor suppressor gene, inhibiting cell proliferation and invasion. NDRG1 expression in cancer cells is generally low, but the molecular mechanism is unclear. Aberrant methylation of CpG islands (CGIs) in gene promoter was able to inactivate tumor suppressor genes and activate oncogenes, disordering cell proliferation and apoptosis, playing a promotion role in tumor occurrence and progression. The present study was performed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
(26 reference statements)
2
29
0
Order By: Relevance
“…Thus, restoring normal WIF-1 expression may downregulate the Wnt signaling pathway and inhibit the progression of lung cancer. In human tumors, abnormal methylation of CpG islands in promoter regions results in a suppression of the transcriptional activity of tumor suppressor genes (35)(36)(37). Previous studies have demonstrated that numerous tumor suppressor genes associated with lung cancer are downregulated via methylation of the promoter region (23,35,38).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, restoring normal WIF-1 expression may downregulate the Wnt signaling pathway and inhibit the progression of lung cancer. In human tumors, abnormal methylation of CpG islands in promoter regions results in a suppression of the transcriptional activity of tumor suppressor genes (35)(36)(37). Previous studies have demonstrated that numerous tumor suppressor genes associated with lung cancer are downregulated via methylation of the promoter region (23,35,38).…”
Section: Discussionmentioning
confidence: 99%
“…N-myc downstream-regulated gene 1 ( NDRG1 ) plays a potent role in modulating metastatic ability in multiple types of solid tumor including CRC [ 16 , 17 ], breast cancer [ 18 , 19 ] and prostate cancer [ 20 , 21 ]. Also, NDRG1 has been linked to many cellular processes including cell cycle, apoptosis, and cellular differentiation [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metastasis suppressor, N-myc downstream regulated gene 1 (NDRG1), was found to play an important role in PCa progression, being reduced in PCa compared to adjacent normal tissues. [5][6][7] Increasing NDRG1 expression in PCa cells had several effects, including the inhibition of (1) proliferation;…”
Section: Introductionmentioning
confidence: 99%
“…(2) the epithelial to mesenchymal transition (EMT), and (3) cell migration and invasion in vitro and metastasis in vivo. [5][6][7][8][9][10][11] NDRG1 also inhibits major oncogenic signaling pathways including EGFR and its downstream MAPK signaling, as well as the PI3K/AKT pathway in cancer cells. 10,12,13 Considering the role of NDRG1 in PCa, agents that can upregulate this protein could be highly efficacious against this disease.…”
Section: Introductionmentioning
confidence: 99%